2015
DOI: 10.1158/1078-0432.ccr-14-2947
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-374b Suppresses Proliferation and Promotes Apoptosis in T-cell Lymphoblastic Lymphoma by Repressing AKT1 and Wnt-16

Abstract: Purpose: Deregulation of microRNA (miRNA) has been extensively investigated in both Hodgkin and non-Hodgkin lymphomas (NHL); however, little is known about the roles of miRNAs in T-cell lymphoblastic lymphoma (T-LBL). The aim of the present study was to investigate the potential roles of miR-374b in the development and treatment of T-LBL.Experimental Design: MiRCURY LNA array was used to generate a miRNA-expressing profile. Real-time quantitative PCR and immunohistochemistry (IHC) were applied to detect the ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 47 publications
1
29
1
Order By: Relevance
“…Accumulating evidence has illustrated that miR‐374b is associated with cancerogenesis, in instances such as colorectal cancer study, where the expression of miR‐374b has been reported to be down‐regulated highlighting it as a potential biomarker for colorectal cancer (Wu et al, ). Qian et al () discussed that miR‐374b inhibits cell proliferation and induce cell apoptosis by suppressing the levels of AKT1 and Wnt‐16 in the AKT signaling pathway in patients with T‐cell lymphoblastic lymphoma. Lu et al () provided an analysis indicative of the notion that miRNA‐374b may affect the development of triple‐negative breast cancer through its regulation of certain central pathways, involving that of fibroblast growth factor and transforming growth factor.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has illustrated that miR‐374b is associated with cancerogenesis, in instances such as colorectal cancer study, where the expression of miR‐374b has been reported to be down‐regulated highlighting it as a potential biomarker for colorectal cancer (Wu et al, ). Qian et al () discussed that miR‐374b inhibits cell proliferation and induce cell apoptosis by suppressing the levels of AKT1 and Wnt‐16 in the AKT signaling pathway in patients with T‐cell lymphoblastic lymphoma. Lu et al () provided an analysis indicative of the notion that miRNA‐374b may affect the development of triple‐negative breast cancer through its regulation of certain central pathways, involving that of fibroblast growth factor and transforming growth factor.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, miRNAs bind to messenger RNAs’ (mRNAs) 3′ untranslated region (3′ UTR), which result in the degradation or translated inhibition of mRNA [5]. Emerging evidence suggests that altered expressions of miRNAs are implicated in various tumor biological process, such as cell growth, proliferation, angiogenesis, migration, invasion and so forth, via regulating targeted genes, [68].…”
Section: Introductionmentioning
confidence: 99%
“…Here, it was found that miR‐374b overexpression promoted p53 expression in NSCLC. At the same time, many studies have shown that miR‐374b exerts its effect by inhibiting the expression of target genes, such as AKT1 and PTEN . In this study, it was found that miR‐374b directly targets ITGB1.…”
Section: Discussionmentioning
confidence: 55%